Nonlinear analysis of RC columns using the Drucker-Prager model - Arslan, Guray; Hacisalihoglu, Melih (Journal of Civil Engineering and Management, 2013)
This paper aims to investigate the correct prediction of load carrying capacity of reinforced concrete (RC) columns. Although substantial experimental and analytical researches have been conducted to model and simulate the response of concrete, little success has been achieved for the general description of the failures of RC columns subjected to bending and axial load. In order to predict the load carrying capacity of RC column, this paper introduces a new relationship for calculating the cohesion parameter of Drucker-Prager criterion. The relationship is developed from a parametric study of a large number of nonlinear finite element analyses of RC columns to account for the parameters. Incorporating these parameters into the failure criterion of concrete, the failure cone of Drucker-Prager model is enforced to approximate and coincide with the whole compressive meridian of the criterion up to the analytically predicted point of the load carrying capacity in the failure analyses. The proposed approach is compared with other approaches using the available column test data to demonstrate how accurately it predicts the load carrying capacity. It is shown that the proposed approach fit quite well to the experimental results of 28 specimens tested by four different researchers.